Validation of turbulence models for dense effluent discharged from circular and square nozzles with a discharge angle of 45 degrees - V. Babaiynejad; R. Haji Seyed Mohammad Shirazi (مهندسی عمران شریف, 2023)
Today, due to the lack of potable water resources in different areas for urban and rural development, serious problems arise in the field of water resources management and supply. One solution to help solve this problem in coastal areas is the use of water desalination systems. The construction of these projects, in addition to the positive effects they have on water supply, can also lead to environmental problems and change the natural state of the area being used. Therefore, efforts should be made to minimize these negative effects. Given the limitations and high costs of laboratory studies, numerical models are necessary to reduce costs. This research focuses on the validation of the SST (k-ω), Standard (k-ε), and RNG (k-ε) turbulence models using ANSYS-FLUENT software to investigate the behavior of saline effluent discharged from circular nozzles and square nozzles (with a discharge angle of 45 degrees). For this purpose, the results of SST, Standard, and RNG models are compared with the results of different studies. To simulate the behavior of the effluent, the model geometry was first designed in SPACE-CLAIM software, and then meshed using ANSYS-MESHING. Short meshes were used near the discharge site, and the length of the meshes increased as the distance from the discharge site increased. After meshing, the model was entered into the FLUENT software for quantification. The Velocity Inlet boundary condition was used for the nozzle opening, the No Slip boundary condition was used for the bed of the discharge area, and the Symmetry boundary condition was used for the walls around the discharge area. The results of turbulence models are more reliable than the results of integral models due to the consideration of flow turbulence. Based on the results, turbulence models are a suitable tool for predicting the behavior of concentrated wastewater discharged from circular and square nozzles. Standard and RNG models have similar behavior, and their results are more reliable compared to SST model results. The RNG model estimates the dilution value with a smaller difference compared to other models and is recommended as the best model.